2021
DOI: 10.1590/1983-21252021v34n111rc
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Spraying of a Seaweed-Based Biostimulant in Soybean

Abstract: Biostimulants currently available on the market include those containing seaweed extract. There is sufficient scientific evidence to conclude that applying biostimulants to agricultural crops can positively impact plant growth and yield. However, results differ between plants species and environmental conditions. As such, the present study aimed to assess the effects of doses and application times of a biostimulant based on seaweed (Ecklonia maxima) extract on the morphology and yield of soybean crops. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…), number of pods per plant (NPP), number of grains per plant (NGP), 1000-grain mass (TGM), and grain yield (YIEL) according to the application of doses (D) of mixed organomineral fertilizer (OMF), used as a biostimulant, at different phenological stages (PS) in the soybean crop. A divergent result was observed by Meyer et al (2021), who, when conducting a study on the effect of the algae extract-based biostimulant Booster® on soybean crops, observed that there was a significant effect on the number of pods at doses of 0.68 and 0.75 L ha -1 in the application at V 4 and R 1 , and for the number of pods on the branches, the best phenological stage of application was at R 1 , with an increase of approximately 30%. According to these authors, this result probably occurred because, although rainfall was adequate during the experiment, high temperatures were recorded for relatively long periods during the reproductive phase, and the biostimulant may have mitigated the harmful effects of the heat.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…), number of pods per plant (NPP), number of grains per plant (NGP), 1000-grain mass (TGM), and grain yield (YIEL) according to the application of doses (D) of mixed organomineral fertilizer (OMF), used as a biostimulant, at different phenological stages (PS) in the soybean crop. A divergent result was observed by Meyer et al (2021), who, when conducting a study on the effect of the algae extract-based biostimulant Booster® on soybean crops, observed that there was a significant effect on the number of pods at doses of 0.68 and 0.75 L ha -1 in the application at V 4 and R 1 , and for the number of pods on the branches, the best phenological stage of application was at R 1 , with an increase of approximately 30%. According to these authors, this result probably occurred because, although rainfall was adequate during the experiment, high temperatures were recorded for relatively long periods during the reproductive phase, and the biostimulant may have mitigated the harmful effects of the heat.…”
Section: Resultsmentioning
confidence: 93%
“…In this context, applying OMF could mitigate possible stresses especially the abortion of flowers and pods that can occur during the soybean cycle and, indirectly, increase crop yield. Other research has obtained positive results with the use of bioregulators and OMF as biostimulants in other crops (Castro et al, 2019;Torsian et al, 2020;Costa et al, 2022) and in the soybean crop, however, their effects vary depending on the time of application, dose, and cultivar used (Cavalcante et al, 2020;Kovalski et al, 2020;Araújo et al, 2021;Meyer et al, 2021;Cavalcante et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Booster® is composed of 239 g L-1 of algal extract (Ecklonia maxima), 24.4 g L-1 of molybdenum (Mo) and 36.6 g L-1 of zinc (Zn). The algal extract used typically contains 10.7 mg L-1 of auxins and 0.03 mg L-1 of cytokinins (MEYER et al, 2021). The hormones in Booster contribute to plant growth and development and promote the development of reproductive structures, improving flower and fruit set (BUCHANAN; GRUISSEM; JONES, 2015;MEYER et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The algal extract used typically contains 10.7 mg L-1 of auxins and 0.03 mg L-1 of cytokinins (MEYER et al, 2021). The hormones in Booster contribute to plant growth and development and promote the development of reproductive structures, improving flower and fruit set (BUCHANAN; GRUISSEM; JONES, 2015;MEYER et al, 2021). Mo acts as a cofactor of nitrate reductase and can increase nitrogen assimilation, especially in nonnodulating plants such as tomato, where most of the nitrogen occurs in the form of nitrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation